2022
DOI: 10.1186/s12906-022-03579-0
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide leads to proteomic differences in thyroid cancer cells and promotes apoptosis

Abstract: Background Parthenolide has anti-inflammatory, immunomodulatory and anti-cancer activities. But its effect on thyroid cancer cells is still largely unknown. Methods Label-free quantitative proteomics and bioinformatics analysis were used to investigate the differentially expressed proteins and their functions in thyroid cancer treated with parthenolide and control pair. Hoechst 33258 fluorescent staining and Annexin V-FITC/PI double staining flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…It has found that amino acid metabolism and glycerphospholipid metabolism were the most important metabolic pathways [5]. We have demonstrated that parthenolide leaded to proteomic differences in BCPAP cells before [13].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…It has found that amino acid metabolism and glycerphospholipid metabolism were the most important metabolic pathways [5]. We have demonstrated that parthenolide leaded to proteomic differences in BCPAP cells before [13].…”
Section: Discussionmentioning
confidence: 74%
“…These results indicated that parthenolide could inhibit the development and proliferation of PTC cells by accelerating oxidative stress response and metabolic imbalance, especially in amino acid and lipid changes [5,12]. Then we demonstrated that parthenolide could lead to proteomic differences in PTC cells (BCPAP cells) [13].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Sufficient cell samples were divided into 12 groups. According to the appropriate concentration (IC50) explored in the preliminary experiment [ 13 ], parthenolide was dissolved in 0.05% DMSO and diluted with PBS to 10 μM and was added to each treatment group ( n = 6) for 24 h, and 6 control groups were added with the same amount of complete culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…These findings indicate that parthenolide can inhibit the growth and proliferation of PTC cells by enhancing oxidative stress response and metabolic imbalance, particularly in terms of amino acid and lipid changes [ 5 , 12 ]. Furthermore, we demonstrated that parthenolide can lead to proteomic differences in PTC cells (BCPAP cells) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%